Hybridization and Cultural Transformation in No Longer at Ease and Arrow of God - Sarfraz, Haroon (JELLL, 2023)
In postcolonial studies, “Hybridization” refers towards the blending of different cultures and beliefs in a single society. Chinua Achebe’s novels No Longer at Ease and Arrow of God have been analysed here in which the native colonized people entangle in hybridity after the intervention of colonial forces along with their culture and religion. The present article pores over the fact that the colonized people face ultimate loss at personal and social levels by being entangled in two opposite cultural and religious beliefs. They adopt the indigenous and the foreign culture and beliefs according to their personal interests and benefits. The study is based on Homi K. Bhabha’s theory of hybridity in The Location of Culture. The textual analysis illustrates that the colonial administration is not only responsible for the effects of hybridization; rather the approaches of the natives also play a significant role in downfall of indigenous culture and religion. The hypothesis is accomplished by discussing the instances of hybridization in the novels and it is demonstrated that this hybrid approach of the local people affects their individual and collective lives.